2002
DOI: 10.1080/jmf.11.5.329.332
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal anemia and iron deficiency on fetal erythropoiesis: comparison between serum erythropoietin, hemoglobin and ferritin levels in mothers and newborns

Abstract: Although cord hemoglobin and mean corpuscular volume were not affected by maternal anemia, increased cord serum erythropoietin levels related to low maternal hemoglobin levels suggest an induced fetal erythropoiesis in maternal anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 9 publications
0
16
1
1
Order By: Relevance
“…In contrast to the findings of this study, other studies conducted both within and outside Africa have found negative or no significant associations between maternal and infant anemia status [27,32,40,41]. Erdem et al ., [41] observed from their study in Turkey that cord hemoglobin and mean corpuscular volumes were not affected by maternal anemia status. According to them, high serum erythropoietin levels were associated with low maternal hemoglobin levels and suggested that maternal anemia rather induces fetal erythropoiesis.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings of this study, other studies conducted both within and outside Africa have found negative or no significant associations between maternal and infant anemia status [27,32,40,41]. Erdem et al ., [41] observed from their study in Turkey that cord hemoglobin and mean corpuscular volumes were not affected by maternal anemia status. According to them, high serum erythropoietin levels were associated with low maternal hemoglobin levels and suggested that maternal anemia rather induces fetal erythropoiesis.…”
Section: Discussioncontrasting
confidence: 99%
“…[5][6][7][8][9][10][11] However, some investigators could not find any relationship between maternal and fetal iron nutriture, thereby concluding that the fetus continues to extract iron efficiently from the mother regardless of her iron balance. [12][13][14][15][16][17] However, these studies did not include a sufficient number of pregnant women with severe anemia. Moreover, these studies also did not examine the effect of simultaneously occurring maternal malnutrition on fetal iron status.…”
Section: Discussionmentioning
confidence: 99%
“…Although serum ferritin levels are elevated in the fetus compared with the mother, the fetal iron stores correlate well with the iron stores of the mother (Milman et al 1987). In anemic mothers with iron deficiency, the fetal ferritin levels remain 10 times higher than the maternal ferritin at the time of delivery (Erdem et al 2002). At birth, the fetal red cell mass is ~50 mL/kg (Phillips et al 1986), compared with 25 – 30 mL/kg in adults (Fairbanks et al 1996).…”
Section: Major Causes Of Iron Deficiency Anemiamentioning
confidence: 99%